Analisis Kajian Diferensiasi dan Diversifikasi Kurikulum di Indonesia - Cindy Desiana; Rosatria Rahmatika; Ratna Sari Dewi (Departement of Mathematics Education, 2023)
The curriculum is the main component of systematic and effective learning in formal education, because learning activities are done by teachers with the help of the curriculum. The curriculum contains learning competencies that serve as a path or trajectory that must be traveled by Indonesian students to achieve the ultimate goal of their education. Curriculum differentiation and diversification are two important concepts used in education to respond to the diversity of students' abilities, interests and learning styles. This article analyzes the results of studies on curriculum differentiation and diversification based on a literature review. The findings of this study found that curriculum differentiation and diversification have important roles, both of which can develop students' interests, motivation and potential in the development of local content in their respective regions.